ATRT-06. CLINICAL AND MOLECULAR RISK FACTORS IN CHILDREN WITH ATYPICAL TERATOID/RHABDOID TUMOUR (AT/RT) - EVIDENCE FROM THE EU-RHAB REGISTRY. Issue 2 (22nd June 2018) - Fruehwald, Michael; Hasselblatt, Martin; Schneppenheim, Reinhard; Nemes, Karolina; Bens, Susanne; Johan, Pascal; Hauser, Peter; Quiroga, Eduardo; Solano-Paez, Palma; Biassoni, Veronica; Gil-da-Costa, Maria Joao; Perek-Polnik, Martha; et al.
Abstract: AT/RT is a challenging entity due to a dearth of controlled clinical trials and lack of biological samples. We aimed to identify clinical and molecular risk factors in a carefully characterised series of AT/RT. METHODS: We enrolled 142 patients from 13 European countries (06/2009 to 08/2017). Median age at diagnosis was 17, 5 months (25 th /75 th percentile: 9/26, 5 months). Therapy followed a consensus regimen. Tumors were investigated for SMARCB1 and SMARCA4 mutations using FISH, MLPA and/or sequencing (n=87/142). Blood was examined for germline mutations (GLM) (n=114/142). Molecular subgroups (ATRT-TYR, -SHH or -MYC) were determined in tumors using Illumina BeadChip based DNA-methylation profiling (n=102/142). RESULTS: Preliminary 5y-OS- and EFS-estimates of this cohort are 20 ± 5% and 26 ± 5%. In a multivariate model, patients (a) below 1 year at diagnosis with (b) M+-disease, (c) synchronous tumours and (d) incomplete resection (no GTR) had the worst prognosis (p<0.05). Most samples had allelic somatic partial/whole gene deletions (55%), while SNVs were observed in 45%. GLM were detected in 26%. Subgroup analyses detected 57% ATRT-SHH, 30% ATRT-TYR, and 13% ATRT-MYC tumors. Children of the TYR-subgroup had a superior outcome. CONCLUSION: Patients can be divided into two defined risk strata: a) infants with metastatic or synchronous tumors and potentially a GLM and/or features of the non-TYR subgroups; b) older patients with a GTR who achieve a CR. This risk model warrants validation and expansion within future clinical trials. EU-RHAB is supported by grants to MCF by the "Deutsche Kinderkrebsstiftung" DKKS 2010.03 and the parents organization Lichtblicke, Augsburg.